2011
DOI: 10.1143/apex.4.115104
|View full text |Cite
|
Sign up to set email alerts
|

Controls over Structural and Electronic Properties of Epitaxial Graphene on Silicon Using Surface Termination of 3C-SiC(111)/Si

Abstract: Epitaxial graphene on Si (GOS) using a heteroepitaxy of 3C-SiC/Si has attracted recent attention owing to its capability to fuse graphene with Si-based electronics. We demonstrate that the stacking, interface structure, and hence, electronic properties of GOS can be controlled by tuning the surface termination of 3C-SiC(111)/Si, with a proper choice of Si substrate and SiC growth conditions. On the Si-terminated 3C-SiC(111)/Si(111) surface, GOS is Bernal-stacked with a band splitting, while on the C-terminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 27 publications
2
49
0
2
Order By: Relevance
“…Most of the works employing either 3C-SiC substrates or 3C-SiC templates on Si(111) for the growth of graphene focused on Si-face material. [8][9][10][11][12] Only two works on C-face graphene grown on 3C-SiC(111) by low-10 and high-temperature 11 sublimation in a ultra-high vacuum and an argon atmosphere, respectively, have been published. Both studies reported that C-face graphene grows without the formation of a buffer layer in similarity to the situation for FLG on 4H-and 6H-SiC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the works employing either 3C-SiC substrates or 3C-SiC templates on Si(111) for the growth of graphene focused on Si-face material. [8][9][10][11][12] Only two works on C-face graphene grown on 3C-SiC(111) by low-10 and high-temperature 11 sublimation in a ultra-high vacuum and an argon atmosphere, respectively, have been published. Both studies reported that C-face graphene grows without the formation of a buffer layer in similarity to the situation for FLG on 4H-and 6H-SiC.…”
mentioning
confidence: 99%
“…We also note the absence of the D peak in the Raman spectra of our sample, which is in sharp contrast to all published results for Si-and C-face graphene on 3C-SiC(111), where a very strong D peak is commonly observed. [8][9][10] The D mode is Raman inactive and requires defects to be activated and its intensity with respect to that of the G peak is related to the defect density. From the absence of the D peak in the Raman spectra of our sample, we estimated a lower limit of the average distance between defects in the C-face graphene on 3C-SiC (111) to be !100 nm.…”
mentioning
confidence: 99%
“…Because of the higher lateral resolution and ability to perform photoemission spectroscopy on the micrometer-submicrometer scale, the apparatus is used for many studies in a variety of fields, not only magnetism. For example, thin-film/ semiconductor interfaces [Sn/Si, 49) H/Si(100), 50,51) Sb on In/Si(111), 52) and Ag/Si(111) 53) ], the growth of graphene, [54][55][56][57] the growth of high-k Hf film, 58) and the mechanism of switching for resistive random access memory (ReRAM; Pt/CuO/Pt system) 59) have been reported.…”
Section: Methodsmentioning
confidence: 99%
“…1 This is valid also for epitaxial graphene, whose structural coherency with 3C-SiC(111) makes it a promising material for next-generation nano-electronic devices. 13,14 Nevertheless, epitaxial growth onto 3C-SiC/Si is still affected by factors such as crystalline defects in the 3C-SiC films and surface roughness. It is well known that 3C-SiC heteroepitaxy on Si is typically characterized by a large number of crystallographic defects such as stacking faults, dislocations, and twins.…”
Section: Introductionmentioning
confidence: 99%